Silica Thin-Layer Chromatographic Studies of Surfactants with Mixed Aqueous-Organic Eluents Containing Thiourea: Simultaneous Separation of Co-existing Cetyltrimethylammonium Bromide, Dodecyltrimethylammonium Bromide, and Polyoxyethylene (20) Sorbitan Monolaurate - Bhawani, Showkat Ahmad; Ali, Mohammad (Oxford University Press, 2008)
Silica thin-layer chromatography of three surfactants using various solvent systems is described. The mutual separation of coexisting cetyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), and polyoxyethylene (20) sorbitan monolaurate (Tween 20) is achieved on silica layer using 5% aqueous thiourea–acetone–methanol (60:20:20,v/v/v) as the mobile phase. The effect of the carbon chain length of alcohols (methanol, ethanol, n-propanol, and n-butanol) on the mobility of these surfactants is examined on silica layers. The comparative study is performed with sulfur- (thiourea) and oxygen- (urea) containing compounds in the eluent on the mobility as well as on the separation of co-existing CTAB, DTAB, and Tween 20. The interference on the resolution of the mixture of CTAB, DTAB, and Tween 20, due to presence of metal cations as impurities, is also examined. The limits of detection of CTAB, DTAB, and Tween 20 are estimated.